The Social Identity Change of Little Bee as the Main Character in Chris Cleave’s The Other Hand - Riska Hendika Rani (Universitas Sebelas Maret, 2020)
This research examines Little Bee’s social identity change based on Chris Cleave’s novel entitled the Other Hand. The object of this research focuses on the Little Bee’s social identity change. The method used in this research is critical reading. To collect the data, the researcher did some steps including reading the novel closely and intensively, making notes, visiting library, and exploring the data from the internet which are related to the topic. In analyzing the data, the researcher used descriptive qualitative method.After conducting the research, the researcher got several research findings. They are: 1). The reason of Little Bee’s social identity change are her envy towards British people’s easy life, her needs to tell her sad story, her will to survive, and her desire to overcome her past. 2). The way Little Bee learns her new identity is by reading, such as novels and newspaper, practicing how to pronounce and speak, looking for difficult words in her dictionary in order to learn the language, and learning the British life by watching television and reading books to understand the British lifestyle.